Fifty years of shape grammars: A systematic mapping of its application in engineering and architecture. (March 2023) - Haakonsen, Sverre Magnus; Rønnquist, Anders; Labonnote, Nathalie
Shape grammars allow a designer to explore a diverse and broad design space. Especially among architects and engineers, the opportunity to evaluate numerous alternatives in the conceptual phase facilitates creativity. Since the introduction of shape grammars 50 years ago, significant research and development have been performed: new applications, combinations with optimisation and integration in digital environments, among others. Consequently, there is a need to map the existing literature to encourage further progress in the field and a lower threshold for those interested in learning more about shape grammars. This study, therefore, presents a systematic mapping of shape grammars in architecture and engineering. Mapping is performed by identifying a query of relevant keywords used in five databases, with the results forming the basis of the mapping. Each of the included articles is then screened to filter out those that do not fit the content criteria. The remaining publications are then evaluated and organised based on the attributes' application, research type, implementation, engineering and optimisation . The outcome is organised in explanatory illustrations and tables. The final discussion highlights the extensive work performed with shape grammars in the generation of two-dimensional floor plans, an increase in digital development in recent years and the need for further research. The findings indicate a gap between the state of the art and the necessary level of applicability for shape grammars to be an attractive design tool, especially for non-experts.